ANALISIS PENGARUH BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA PEGAWAI BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN ROKAN HULU - Erpanda, Dedi (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
This Research aim to to To to know organizational culture of Officer Of Office Body Disaster of Penangulangan Area Sub-Province of Rokan Pate;Upstream. Method in this research is observation method, kuisioner, this research office archives and document is done/conducted by in Body office penanggulangan of Sub-Province area disaster of Rokan Hulu start October month;moon - December 2015. With amount of population 61 people, Instrument at this research is Test Validity and Test of Reabilitas, and Technique Analyse its Data is quantitative descriptive with test of signivikan. From result of res earch got by using program of SPSS fersi 18 got that Result of calculation of statistic show f value count/calculate = 22.006 with signifikan 0.000 < 0,05. F Value of[is tables of = 0.272. Thereby f value count/calculate = ( 22.006) bigger than F of is tables of (0.254). matter this means that hypothesis expressing that by simultan organizational culture have influence which is signifikan to satisfaction of officer job/activity accepted. Model equation of rekresi able to be written from the result in the form of equation of Standard regresi of Dized shall be as follows Y= 37.603+.552X+e. To the can know that value of r count/calculate bigger than r of[is tables of to each;every raised question item to responder.Pursuant to that if r niali count/calculate bigger than r of is tables of hence data of kuisioner told valid because item of peryataan have above 0,254, above can know that value of r count/calculate bigger than r of is tables of to each;every raised question item to responder.Pursuant to that if r niali count/calculate bigger than r of is tables of hence data of kuisioner told valid because item.